ANALISIS EFISIENSI EKONOMI USAHATANI TEMBAKAU RAKYAT DI KABUPATEN LOMBOK TIMUR - Septiadi, Dudi; Utama FR, Aeko Fria (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2023)
This study aims to analyze the economic efficiency of smallholder tobacco farming in East Lombok District. People's tobacco is one of the important agricultural commodities in the area. The method used in this study was a field survey and primary data collection from smallholder tobacco farmers. The research sample was selected using a simple random method from the farmer population in Suralaga District, East Lombok Regency. The villages that were used as research samples were Waringin Village and Suralaga Village. The data collected will include information on production costs, income, production factors used, and commodity prices for people's tobacco. Descriptive-quantitative is the method used in this study. Economic efficiency analysis will be carried out using the R/C ratio analysis. The results of the analysis show that smallholder tobacco farming in the study area has been running efficiently (R/C ratio: 2.66). Obstacles faced by many farmers in smallholder tobacco farming are extreme weather/climate changes, irrigation problems, and access to fertilizers.